BEGINNINGS OF THE NEOLITHIC IN TRANSYLVANIA: A FRAGMENTARY FIGURINE FROM LIMBA-OARDA DE JOS-BORDANE (ALBA COUNTY) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2026)
The discovery of a fragmentary figurine within a sunken structure in the Bordane sector of the Limba-Oarda de Jos archaeological site (Alba County) contributes to the understanding of the cultural and chronological position of the earliest Early Neolithic horizon in the Middle Mureș Valley. The fragmentary piece, of which only the lower part (the legs and the beginning of the abdomen) has been preserved and which appears to have been intentionally broken, represents a female figurine with evident steatopygia features. The modelling of its forms and the treatment of its surfaces reveal distinctive traditions and techniques commonly found among anthropomorphic representations discovered at contemporary sites associated with the earliest phase of the Starčevo-Criș Cultural Complex (phase I), alternatively known as: the Gura Baciului group (of the Protostarčevo Culture), the Precriș Culture, or the more recently accepted term: White-on-Red Painted Pottery (WRPP). The anthropomorphic figurative art characteristic of the material culture in the settlements of the first Neolithic colonists north of the Danube, though relatively scarce, preserves archetypal traditions specific to the original areas of southern Balkan Peninsula and even Anatolia. The typological and stylistic analysis of the artifact is complemented by a thorough investigation of the clay paste used in its modelling, as well as the surface treatments applied (slip coating, burnishing, painting etc.), revealing previously undocumented aspects of the piece’s manufacture. Based on the obtained data, the authors raise several questions regarding the figurine's origin - namely, whether it should be interpreted as a locally produced item or as an artifact crafted in the original homelands of the earliest waves of Neolithization in the territories south of the Danube.